Exploratory Comparative Review of the Revolving Door Phenomenon in Government Across Four Aspects - Hwang, Kwangseon (Animo Repository, 2024)
The purpose of this study is to compare the revolving door phenomenon across different types of literature and research. This investigation was conducted through a comprehensive literature review encompassing four categories: legal, academic, governmental, and political-economic research. The review of these various bodies of literature unveiled differing approaches to addressing the revolving door phenomenon. Governmental studies primarily centered on the operational aspects of government and scrutinized whether resources were potentially misused or squandered due to the revolving door. Conversely, legal and academic research placed their emphasis on ethical concerns, conflicts of interest, and the public’s perception of government. They explored the possibility that political appointees might prioritize their own careers over the needs and desires of citizens. The diverse array of issues and concerns examined in the reviewed research offered a comprehensive perspective on the revolving door phenomenon. In the realm of political-economic literature, the revolving door was seen as a means to attract talent and expertise to government roles. However, it also raised apprehensions about conflicts of interest and the potential for regulatory capture.